Composition and Diversity of the Nymphalid butterfly (LEPIDOPTERA: NYMPHALIDAE) in South Sumatra, Indonesia - Syafrina lamin; Elsa Claudia; Juswardi Rasidin; Rahmat Pratama (Penerbit Universiti Kebangsaan Malaysia, 2024)
Research focusing on the composition, distribution, and diversity of nymphalid butterfly species in different habitat characters is very important. This information is important for the conservation of endangered and endemic species. The research objective was to determine the diversity of butterflies, especially on the Nymphalidae family, which includes structure, composition and distribution by analyzing the species dominance index (D), Shannon diversity index (H'), and evenness index (E). This research was conducted, taking place in the prosperous Dempo Village area, North Dempo District, Pagar Alam City, South Sumatra, Indonesia. Determination of butterfly observation locations was carried out by purposive random sampling method at five locations with different environmental characteristics, namely location of the Rimau Monument, Kampung Empat, Mangkok Waterfall, Dew Waterfall, and Seven Kenanga Waterfall. The collection was carried out directly in the observation area using insect net and using 30 bait traps containing rotten bananas and pineapples at each location where six traps were installed. Sampling was carried out from 08.00 to 16.00 for 2 months. Seven sub-families of nymphalid butterflies were found consisting of 19 genera, 24 species and 641 individuals. The species obtained were Cyretis maenalis, Euripus nyctelius, Danaus melanippus, Hypolimnas anomala, Hypolimnas bolina, Junonia iphita, Junonia orithya, Lethe confuse, Lethe blooma, Mycalesis perseus, Neptis hylas, Polyura hebe, Polyura moori, Euthalia monima, Lexias pardalis, Symbrenthia lilaea, Ypthima pandocus and Vanessa cardui. The diversity index was between 1.42-2.47 and was highest at the Dew waterfall location. The dominance index value ranges from 0.20-0.55 and the highest is found in the Kampung Empat location, the similarity index value ranges from 0.47 – 0.97, the highest is in the Kampung Empat location. The dominating species in this area are Y. pandocus and V. carduii.